Anne Mette Thorhauge from the Department of Media, Cognition and Communication at the University of Copenhagen talks with Kathleen Tyner and Conceição Costa about opportunities and challenges as games are integrated into the formal learning environment (Revista Lusófona de Educação, 2018)
Anne Mette Thorhauge from the Department of Media, Cognition and Communication at the University of Copenhagen talks with Kathleen Tyner and Conceição Costa about opportunities and challenges as games are integrated into the formal learning environment